PENINGKATAN KEPUTUSAN BERKUNJUNG WISATAWAN MELALUI PENGEMBANGAN CITRA DESTINASI DAN AKSESIBILITAS DI LEMBAH TEPUS BOGOR - Benedicta Jennifer Yosandri; Nova Eviana (Eduturisma, 2022)
Each tourist attraction manager strives to increase tourist visits in order to increase revenue and maintain the sustainability of tourist attraction management. This can be done through the identification of factors that influence the decision of tourists to visit a tourist attraction. This study aims to analyze the influence of destination image and accessibility on visiting decisions in the Tepus Valley Tourist Attraction. The research method is a quantitative descriptive that uses questionnaires as a data gathering tool. A total of 100 tourists were involved as respondents to the study based on the Lemeshow formula, by accidental sampling. Data analysis techniques use multiple linear regression with SPSS ver.20 software. The results showed that the image of the destination and accessibility partially influenced positively and significantly the decision to visit. Simultaneously, destination image and accessibility have a positive and significant effect on visiting decisions. Therefore, the manager of the Tepus Valley Tourist Attraction needs to continue to strive for improvements to the accessibility and image of the destination in order to increase tourist visits.